2015
DOI: 10.5455/ajvs.170301
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements Status and Antioxidants Profile in Ill-thrift Buffalo Calves

Abstract: The goal of the present study was to evaluate some trace element concentrations and the activity of antioxidant systems in ill-thrift calves. A total number of (52) buffalo-calf was subjected to study. Out of them, (37) buffalo-calves had poor coat, poor general body condition score which constituted the ill-thrift group. The remained animals (15) were clinically healthy and kept as control group. Complete blood picture, trace elements profile, serum calcium, phosphorus & magnesium , blood urea nitrogen (BUN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…The pronounced decrease in Cu, Se, and Fe serum levels observed in the emaciated group in this study aligns with Ahmed et al's [55] findings indicating a deficiency in these trace elements can hinder goat growth. In the present study, Zn and Co showed insignificant changes in their levels in the emaciated group despite the established association between Zn and Co with the occurrence of ill-thrift in calves [8,11]. These findings do not rule out the possibility of these minerals playing a role in causing ill-thrift in goats.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The pronounced decrease in Cu, Se, and Fe serum levels observed in the emaciated group in this study aligns with Ahmed et al's [55] findings indicating a deficiency in these trace elements can hinder goat growth. In the present study, Zn and Co showed insignificant changes in their levels in the emaciated group despite the established association between Zn and Co with the occurrence of ill-thrift in calves [8,11]. These findings do not rule out the possibility of these minerals playing a role in causing ill-thrift in goats.…”
Section: Discussioncontrasting
confidence: 97%
“…This study suggested that Fe deficiency may contribute to ill-thrift in goats. The significant decrease in serum Cu levels observed in both emaciated and thin groups in this study aligns with Ismaeel et al's finding of a significant decrease in serum Cu levels of ill-thrift calves compared to the control ones [11]. Borghese [50] and Sadiek et al [51] similarly noted Cu deficiency impacting growth of buffalo and buffalo calves.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…So, Pb is accumulated in roots in higher concentrations and less shoot of forages Sharma and Dubey (2005). This concentration of Co in blood was found in accordance with the results given by Ismael et al (2015). The cobalt (Co) level in hair of ruminants was greater as compared to observations given by Hejna et al (2018).…”
Section: Discussionsupporting
confidence: 87%